2020
DOI: 10.1038/s41398-020-01089-6
|View full text |Cite
|
Sign up to set email alerts
|

Gamma oscillations predict pro-cognitive and clinical response to auditory-based cognitive training in schizophrenia

Abstract: Cognitive impairments are pervasive and disabling features of schizophrenia. Targeted cognitive training (TCT) is a “bottom-up” cognitive remediation intervention with efficacy for neurocognitive outcomes in schizophrenia, yet individual responses are variable. Gamma oscillatory measures are leading candidate biomarkers in the development of biologically informed pro-cognitive therapeutics. Forty-two schizophrenia patients were recruited from a long-term residential treatment facility. Participants were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 70 publications
6
30
0
Order By: Relevance
“…However, as shown by the lack of association between IGFs and processing speed in our sample, it is possible that connection can be observed in clinical populations with clearly impaired cognitive processing, or be highly modality-specific (i.e., auditory response is associated to the performance of auditory tasks). The latter assumption connects with a recent suggestion of Molina et al [ 66 ] that evoked gamma may be an index of the brain’s overall “adaptive integrity“ of the lower-level perceptual networks. We tested healthy young participants, and all tasks utilized in the current research were based on visual domain assessment.…”
Section: Discussionsupporting
confidence: 81%
“…However, as shown by the lack of association between IGFs and processing speed in our sample, it is possible that connection can be observed in clinical populations with clearly impaired cognitive processing, or be highly modality-specific (i.e., auditory response is associated to the performance of auditory tasks). The latter assumption connects with a recent suggestion of Molina et al [ 66 ] that evoked gamma may be an index of the brain’s overall “adaptive integrity“ of the lower-level perceptual networks. We tested healthy young participants, and all tasks utilized in the current research were based on visual domain assessment.…”
Section: Discussionsupporting
confidence: 81%
“…The results of mindfulness practice were rather similar to the EEG findings on beta and gamma neurofeedback training (a training aimed at improving beta or gamma power) that showed that 10 days of beta and gamma neurofeedback training led to improved episodic memory among healthy adults (Keizer, Verschoor, Verment, & Hommel, 2010). A similar association between long-term cognitive training and gamma power elevation was also found among the elderly population (Staufenbiel, Brouwer, Keizer, & Van Wouwe, 2014) and patients with Alzheimer's disease (Van Deursen, Vuurman, Verhey, Van Kranen-Mastenbroek, & Riedel, 2008), schizophrenia (Molina et al, 2020), and attention-deficit/hyperactivity disorder (Yordanova, Banaschewski, Kolev, Woerner, & Rothenberger, 2001). Furthermore, the results were consistent with the neuroimaging findings that highly focused participants with 6 weeks of mindfulness training showed better cognitive performance in the Stroop test, in addition to exhibiting higher dlPFC activation (M. Allen et al, 2012).…”
Section: Training Effect Of Mbsrsupporting
confidence: 70%
“…However, this is not completely surprising, since also previous research found that greater service intensity is related to higher rates of improvement in neurocognition and global functioning over time. 61–63 …”
Section: Discussionmentioning
confidence: 99%